In-Vitro study to Assess Effect of a Glide Path on Canal Transportation and Centering Ratio in Double Curved canals. - Raghad Alhalabi; Mohammad Salem Rekab; Khaldaon hossein Alhroob; Maher Al-assaf (University Library System, University of Pittsburgh, 2021)
Objective: In endodontic treatment, creating a glide path became one of the recommended essential principles to obtain a safe preparation as possible; so the aim of the research is to evaluate the efficiency of the R-Pilot system in glide path preparation within the double curved canals. Study design: A laboratory study to assess the efficiency R-Pilot mechanical patency system on the shape marinating of the canal. Those criteria were used to evaluate the change in the original shape of the canal, Canal Transportation and Centering Ratio. The data were analyzed using SPSS V.13 program and the correlation between the variables were defined using descriptive statistics and inductive statistical tests (chi-square, T Student for independent samples, ANOVA). Results: no significant difference between the two glide path creation systems was found in terms of the deviation amount from the canal centric. whereas, between the R-Pilot system and the manual preparation, significant difference was found in the preserving rate of the canal centric at both the coronal area and the entire canal. Conclusion: glide path creation in the previously mentioned methods with confirmation on the importance of the mechanical patency in terms of speed, Reducing the effort and burden imposed on the practitioner compared to the use of manual files. XP Endo shaper had lower deviation values and more ability to save the shape and centric of the canal.